Development of polychormatic irregular waves for testing OWC bidirectional turbines at a land-based test facility - Farman, Judith R.; Teixeira, Joao Amaral; Whidborne, James F.; Mba, David; Natanzi, Shahab (European Wave and Tidal Energy Conference, 2013)
This paper presents the development of a control strategy that allows a dedicated oscillating water column turbine test facility to produce polychromatic waves. This facility allows testing of bi-directional turbines under transient conditions, validation of computational fluid dynamics simulations and testing of turbine control strategies under realistic sea states. The test facility employs a pneumatic wave generator (of unique design) to simulate the air flow of an oscillating water column. This work describes the methodology to create wave time series of various spectra that replicate a range of wave states at various geographical locations employing this rig.